Implementation of Electronic Certificates for Land Ownership Rights in the Dynamics of Law and Globalization - Mustaqim, Mustaqim; Febrianty, Yenny; Ardian, Ardian; Wijaya, Mustika Mega (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The digital transformation has changed various aspects of human life, including in the legal and land administration sectors. In 2023, the government issued Ministerial Regulation Number 3 of 2023 which regulates the issuance of electronic documents in land registration activities, including electronic certificates as a form of land ownership rights. However, the implementation and use of these electronic certificates have raised various questions and debates regarding legal protection for landowners. This research aims to analyze the legal protection provided by electronic certificates to landowners in the digital transformation era based on Ministerial Regulation Number 3 of 2023. The research method used is normative analysis by examining relevant legislation and current literature. The results show that electronic certificates as a form of land ownership rights provide several advantages, such as administrative efficiency, data accessibility, and protection against physical loss risks. However, there are challenges related to data security and integrity, as well as the legal awareness of the community regarding the use of electronic certificates. The use of blockchain technology and data encryption can be solutions to address some of these challenges. Additionally, it is found that legal protection for landowners needs to be enhanced by regulating critical aspects such as the authenticity, integrity, and non-repudiation of electronic certificates. The establishment of strong legal mechanisms in handling dispute resolution is also important to increase public trust in electronic certificates.